Knowledge is power: Issues of measuring training and performance in cycling - Passfield, L.; Hopker, J. G.; Jobson, S.; Friel, D.; Zabala, M. (Journal of Sports Sciences, 2014)
Mobile power meters provide a valid means of measuring cyclists` power output in the field. These field measurements can be performed with very good accuracy and reliability making the power meter a useful tool for monitoring and evaluating training and race demands. This review presents power meter data from a Grand Tour cyclist`s training and racing and explores the inherent complications created by its stochastic nature. Simple summary methods cannot reflect a session`s variable distribution of power output or indicate its likely metabolic stress. Binning power output data, into training zones for example, provides information on the detail but not the length of efforts within a session. An alternative approach is to track changes in cyclists` modelled training and racing performances. Both critical power and record power profiles have been used for monitoring training-induced changes in this manner. Due to the inadequacy of current methods, the review highlights the need for new methods to be established which quantify the effects of training loads and models their implications for performance.